Investigation of Flavonoid Levels of Black Rice from Rice (Oryza sativa L.) on Sumba Island - Ghello, Jennilien Merinda; Bani, Gregorio Antonny (Jurnal Biologi Tropis, 2025)
Rice (Oryza sativa L.) is Indonesia’s main cereal crop and is classified into three types based on color: white, red, and black. Among these, black rice has the highest antioxidant content. As a secondary metabolite, antioxidant levels vary depending on regional characteristics. On Sumba Island in East Nusa Tenggara, black rice known as Wojalaka grows across four districts with distinct environmental conditions. This study aimed to evaluate the flavonoid content of Wojalaka black rice from these districts. Using UV-Vis spectrophotometry, ground rice samples were extracted via methanol maceration and analyzed through linear regression. The flavonoid levels found were West Sumba (Lamboya) 74.03 µg/L; Southwest Sumba (Kodi) 67.67 µg/L; Central Sumba (Umbu Ratunggai) 31.65 µg/L; and East Sumba (Matawai) 132.16 µg/L. The highest flavonoid concentration was observed in Matawai at 132.16 µg/L, while the lowest was in Umbu Ratunggai at 31.65 µg/L. These results indicate that flavonoid content depends on habitat conditions the drier the environment where the rice grows, the higher its flavonoid levels.